Method for the extraction of high quantity and quality cell-free DNA from amniotic fluid - Lapaire, Olav (2008)
Circulating cell-free fetal deoxyribonucleic acids (cffDNA) are promising biomarkers with various promising clinical applications. Second and third trimester amniotic fluid (AF) is a rich source of cffDNA. Further improvements to the original protocol for the extraction of cffDNA from AF supernatant resulted in statistically significant higher yields of high quality cffDNA, allowing for a substantial majority of samples to be analyzed with subsequent molecular methods (e.g. comparative genomic hybridization [CGH] micro arrays) to further assess for genetic abnormalities. Several advantages have been realized with the optimized protocol. In addition to an improved yield from a greater proportion of samples as compared to the original protocol, the current method, using large silico-membranes, allows for the extraction of cffDNA from up to ten samples in less than three hours. The replacement of the original lysis buffer eliminates the need for a heating bath during the lysis step, and fewer overall steps are involved in the protocol (e.g. to reduce potential contamination). The improvements in the yield with the current protocol make it possible to augment current standard of care through the analysis of this previously unappreciated source of genetic material, and furthermore, will allow for exploration of widely unknown genetic, pathophysiological and kinetic issues of cell-free fetal DNA in amniotic fluid.